PP.06 UK Obstetric Critical Care Provision Remains Unfit For Purpose. (26th April 2013) - Saunders, A; Jones, F; Carlin, A; Scholefield, H; Whitworth, MK
Abstract : Background: Successive confidential enquiries have recommended that obstetric critical care (OCC) patients be cared for in a level 2 setting with adequate facilities and trained staff. In 2007 we conducted the first national survey of UK OCC provision and demonstrated major, potentially life threatening deficiencies. We aim to see if OCC provision in 2012 is fit for purpose. Method: We conducted a validated survey of 227 maternity units in the UK (May-July 2012). Results: 137 questionnaires were returned (response rate-60%). Mean number of deliveries/year was 4076 (200–9867). 57% of units report having designated OCC bed provision (56% in 2007 p = 0.88). Median provision is two beds/unit compared with one in 2007. Nursing care is provided solely by midwives in 71% of units (95% in 2007, p < 0.05). 76% of these midwives have some formal in-house or external OCC training (33% in 2007, p < 0.05). Joint medical care is provided by obstetricians and anaesthetists in 89% of units (72% in 2007, p < 0.05). However, of those units claiming to have designated OCC capacity 32% were unable to provide one or more of the elements required for level 2 care e.g. arterial line management. The main issues identified by responding units remain the need for; better facilities and equipment, formal OCC training, improved staffing. Conclusions: Our survey suggests there is a lack of knowledge about OCC and provision remains unfit for purpose. We remain a long way from providing equity of critical care for pregnant women as recommended by the joint RCOG/RCA document of 2011.